Comparison of pregnancy outcomes and safety between cetrorelix and ganirelix in IVF/ICSI antagonist protocols: a retrospective cohort study - Peng, Xinyue; Lv, Xingyu; Li, Penghao; Li, Yingxing; Hu, Yuling; Zhang, Yi; Li, Yuan (Frontiers in Reproductive Health, 2025)
IntroductionThis study aimed to compare the safety, efficacy, and clinical predictors of live birth outcomes between cetrorelix and ganirelix in GnRH antagonist protocols during controlled ovarian stimulation.MethodsIn this retrospective cohort study conducted at a reproductive medicine center (June 2019–June 2022), 2,365 patients receiving cetrorelix (Group A) and 7,059 patients receiving ganirelix (Group B) were analyzed after 1:3 propensity score matching. Outcomes included LH surge suppression, OHSS incidence, endometrial morphology, embryological parameters, and live birth rates. Multivariate logistic regression identified independent predictors of clinical success.ResultsCetrorelix demonstrated superior LH surge control, with lower incidences of LH ≥10 U/L (4.9% vs. 7.6%, p < 0.001) and LH ratio(trigger day LH Gn day LH) ≥2 (6.1% vs. 9.2%, p < 0.001). Endometrial receptivity was more favorable in Group A, with higher Type A (66.2% vs. 60.1%) and lower Type C morphology (5.3% vs. 6.3%, p < 0.001). Ganirelix showed a higher overall OHSS incidence (1.1% vs. 0.4%, p = 0.01). Live birth rates were comparable (47.2% vs. 49.4%, p = 0.074). Multivariate analysis revealed advanced female age (≥35 years) reduced success (aOR = 0.65, 95% CI 0.57–0.74, p < 0.001), while AMH ≥4 μg/L (aOR = 1.29, 95% CI 1.02–1.64, p = 0.034), and dual embryo transfer (aOR = 1.51, 95% CI 1.38–1.65, p < 0.001) improved outcomes.ConclusionCetrorelix and ganirelix demonstrate comparable live birth rates and embryo quality, yet exhibit distinct safety profiles. Cetrorelix provides superior LH surge suppression and reduced OHSS risk, making it preferable for high-risk patients, while ganirelix may serve cases requiring rapid LH control. Cetrorelix offering enhanced endometrial receptivity (66.2% Type A morphology) and safety advantages. These findings support cetrorelix's role in optimizing ART safety without compromising efficacy.